2014
DOI: 10.1097/ccm.0000000000000128
|View full text |Cite
|
Sign up to set email alerts
|

Hemolysis in Pediatric Patients Receiving Centrifugal-Pump Extracorporeal Membrane Oxygenation

Abstract: Hemolysis during extracorporeal membrane oxygenation with centrifugal pumps was common and associated with a number of adverse outcomes. Risk factors for hemolysis included oxygenator types, mean venous inlet pressure, and mean pump speed. Further studies are warranted comparing pump types while controlling both physical and nonphysical confounders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
148
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(153 citation statements)
references
References 18 publications
3
148
2
Order By: Relevance
“…Similarly, despite improved management of anticoagulation and transfusion in patients on ECMO, thrombosis is a main cause of mortality and morbidity (Oliver, 2009 (Lou et al, 2014). Furthermore, there is an association between haemolysis and circuit thrombosis (Zangrillo et al, 2013).…”
Section: Mechanical Circulatory Supportmentioning
confidence: 99%
“…Similarly, despite improved management of anticoagulation and transfusion in patients on ECMO, thrombosis is a main cause of mortality and morbidity (Oliver, 2009 (Lou et al, 2014). Furthermore, there is an association between haemolysis and circuit thrombosis (Zangrillo et al, 2013).…”
Section: Mechanical Circulatory Supportmentioning
confidence: 99%
“…Recent studies have shown a clear association between extracellular Hb and the development of postoperative acute kidney injury after surgery on CPB [41][42][43][44], suggesting a crucial role in the induction of inflammation and oxidative stress by Hb and its metabolites [45]. In clinical studies on paediatric and adult ECMO patients increased levels of plasma extracellular Hb are associated with increased mortality [43,46]. …”
Section: Extracorporeal Circulation and Haemolysismentioning
confidence: 99%
“…1 Increasing incidence of hemolysis and thrombosis is associated with morbidity and mortality in patients on extracorporeal membrane oxygenation (ECMO). 2 Prevention of circuit clotting in ECMO can improve clinical outcome.…”
Section: Introductionmentioning
confidence: 99%